Revisión bibliográfica sobre la caracterización del aceite de semilla de Sacha Inchi (Plukenetia volubilis L.) y las propiedades de sus emulsiones (2021)
In recent years, Sacha inchi (Plukenetia Volubilis L.) seed oil has drawn interest within the food industry because of its potential as a functional food due to its high content in components such as [¿, y, o] tocopherols and fatty acids such as linoleic, ¿-linolenic, and oleic acid. Per this, a bibliographic review was made regarding the physicochemical characterization of sacha inchi oil, its composition, and potential benefits on human health. In the same way, literature regarding the use of emulsification techniques for oil encapsulation was investigated.